Three decades of sustainable development – emergence, domination, weaknesses and perspective - Vujić, Marko (Sociološki pregled, 2023)
The paper is aimed to perceive critically the three-decade concept of sustainable development at several levels, and, accordingly, it is divided into three parts. The first one is dedicated to the specific features of the emergence of this concept in the initial period 1983-1992 and the first developmental period 1992-2000. A special emphasis is laid on the theoretical distinction and domination of the concept of sustainable development in relation to the then existing forms, such as ecological modernization. The second part of the paper continues the identification of the developmental stages within the scope of the Millennium Goals 2000–2015, with a central critical focus on the achieved results. The third part of the paper covers the current stage of the Sustainable Development Goals (SDGs) envisaged for the period 2015–2030, and particularly points to the quantitative faults and inconsistencies in the methodology of evaluation, as well as measurement of the fulfilment of the goals themselves. The analytical apparatus points ty qualitative and quantitative methods to the chronically faulty set of instruments of sustainable development due to which the ecological component as the first among the equal is derogated to the level of the least importance, which is contrary to the founding principles of this concept.
Keywords: ecology; the United Nations; sustainable development; Sustainable Development Goals